2014
DOI: 10.1111/1365-2664.12212
|View full text |Cite
|
Sign up to set email alerts
|

Roosting behaviour and habitat selection of Pteropus giganteus reveal potential links to Nipah virus epidemiology

Abstract: Summary 1. Flying foxes Pteropus spp. play a key role in forest regeneration as seed dispersers and are also the reservoir of many viruses, including Nipah virus in Bangladesh. Little is known about their habitat requirements, particularly in South Asia. Identifying Pteropus habitat preferences could assist in understanding the risk of zoonotic disease transmission broadly, and in Bangladesh, could help explain the spatial distribution of human Nipah virus cases. 2. We analysed characteristics of Pteropus giga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 37 publications
6
72
1
1
Order By: Relevance
“…However, consumption of date palm sap, as well as hunting bats for bushmeat, are relatively common practices throughout Bangladesh (Openshaw et al 2016), and yet the majority of outbreaks have occurred in central and northwest Bangladesh, to the extent that these regions are colloquially referred to as the ‘Nipah belt’. This has provoked attempts to correlate ecological factors in these regions with the high outbreak prevalence (Hahn et al 2014a; Hahn et al 2014b). One analysis found that Nipah belt villages have significantly higher population densities, and occur in regions where forest land is more fragmented, suggesting these factors could promote NiV outbreaks (Hahn et al 2014b).…”
Section: Ecological Factors Driving Zoonotic Paramyxovirus Emergencementioning
confidence: 99%
See 3 more Smart Citations
“…However, consumption of date palm sap, as well as hunting bats for bushmeat, are relatively common practices throughout Bangladesh (Openshaw et al 2016), and yet the majority of outbreaks have occurred in central and northwest Bangladesh, to the extent that these regions are colloquially referred to as the ‘Nipah belt’. This has provoked attempts to correlate ecological factors in these regions with the high outbreak prevalence (Hahn et al 2014a; Hahn et al 2014b). One analysis found that Nipah belt villages have significantly higher population densities, and occur in regions where forest land is more fragmented, suggesting these factors could promote NiV outbreaks (Hahn et al 2014b).…”
Section: Ecological Factors Driving Zoonotic Paramyxovirus Emergencementioning
confidence: 99%
“…One analysis found that Nipah belt villages have significantly higher population densities, and occur in regions where forest land is more fragmented, suggesting these factors could promote NiV outbreaks (Hahn et al 2014b). A similar analysis sought to identify risk factors by better understanding the features of preferred habitats of P. giganteus , a key NiV reservoir bat species – an approach validated by their finding that outbreak villages were 2.6 times more likely to map to a location their model predicts as a likely preferred habitat (Hahn et al 2014a). The major contributing factors determining habitat preference included tree species, forest fragmentation, rainfall, temperature gradients and human disturbance levels.…”
Section: Ecological Factors Driving Zoonotic Paramyxovirus Emergencementioning
confidence: 99%
See 2 more Smart Citations
“…which hosts are potentially involved in transmission (key hosts)?/which species in the ecosystem are infected?epidemiological studies, such as seroprevalence, parasitological and/or molecular typing studies from humans and animals can be used to identify potential hosts.[70,81,9193]comparison of human and veterinary surveillance data can provide early indication that an outbreak of disease in humans may have a zoonotic origin.[94–96]2. is there potential for effective contact between host species and, if so, how do contact rates compare between versus within species?GPS tracking can be used to asses contact between wildlife species and between wildlife and domestic livestock.[94]ecological studies of wildlife hosts can identify potential interspecies transmission pathways to humans.[25]3. is there evidence of cross-species transmission and host shifts?population genomic and genetic studies can type infecting pathogen species and demonstrate gene flow across known host species.…”
Section: Disentangling and Quantifying Transmissionmentioning
confidence: 99%